Identifikasi Potensi Bahaya Kecelakaan Kerja Menggunakan Metode HAZOP dalam Industri Pembuatan Kapal (Studi Kasus : PT NSBL) - Siahaan, Jhon Alfred; Sundari, Susanti; Pratiwi, Mirandhi; Nudin, Burhan (Industrika : Jurnal Ilmiah Teknik Industri, 2025)
Problems that often occur in the work environment include worker attitudes, work environment conditions such as slippery floors and work areas at high places, and the potential for damage to machine components. The potential for work accidents at PT. NSBL was carried out using the HAZOP method. This method identifies various sources of danger. The risk evaluation revealed that high and medium risks dominate, while the K3 program is not optimal. Based on research that has been conducted, there are 5 categories of hazard sources including worker negligence in working, the presence of high voltage electric currents, storage and use of toxic chemicals, and flammable and corrosive materials. Recommendations include increasing K3 training, implementing strict procedures for the use of PPE, improving the work environment, and regular maintenance of equipment. These efforts are expected to reduce the risk of work accidents and increase safety at PT. NSBL. Keywords: HAZOP, Occupational Safety and Health, Potential Hazards